(untitled) (Ciudades, 2017)
The aim of this study was to characterize of Historic Centers from establishing linkages between demographic and housing dynamics, assuming that these dynamics are the result, or more or less direct referrals, the territorial context that welcomes urban that contain them. We adopt, therefore, as a field of analysis, a specific area of the city, one who has purchased its characterization as a historic, considering that the behavior of the field, can be derived very specific consequences will affect the dynamics of the city as a whole. To do this, we will take as a reference to Castilian territory, selecting for study, those containing urban historical areas declared as Cultural Interest.